A contemporary survey of bumble bee diversity across the state of California. Issue 3 (18th March 2022) - Fisher, Kaleigh; Watrous, Kristal M.; Williams, Neal M.; Richardson, Leif L.; Woodard, Sarah Hollis
Abstract: Bumble bees (genus Bombus ) are important pollinators with more than 260 species found worldwide, many of which are in decline. Twenty‐five species occur in California with the highest species abundance and diversity found in coastal, northern, and montane regions. No recent studies have examined California bumble bee diversity across large spatial scales nor explored contemporary community composition patterns across the state. To fill these gaps, we collected 1740 bumble bee individuals, representing 17 species from 17 sites (~100 bees per site) in California, using an assemblage monitoring framework. This framework is intended to provide an accurate estimate of relative abundance of more common species without negatively impacting populations through overcollection. Our sites were distributed across six ecoregions, with an emphasis on those that historically hosted high bumble bee diversity. We compared bumble bee composition among these sites to provide a snapshot of California bumble bee biodiversity in a single year. Overall, the assemblage monitoring framework that we employed successfully captured estimated relative abundance of species for most sites, but not all. This shortcoming suggests that bumble bee biodiversity monitoring in California might require multiple monitoring approaches, including greater depth of sampling in some regions, given the variable patterns in bumble bee abundance and richness throughout the state. Our study sheds light on the current status of bumble bee diversity in California, identifies some areas where greater sampling effort and conservation action should be focused in the future, and performs the first assessment of an assembly monitoring framework for bumble bee communities in the state. Abstract : Bumble bees are important pollinators worldwide, with 25 species occurring in California. We collected 1, 740 bees at 17 sites across California, the first regional study in California in nearly 40 years. Our study sheds light on the current status of bumble bee diversity in California and identifies areas where greater sampling and conservation action should be targeted in the future.